The influence of Sc substitution on the crystal structure and scintillation properties of LuBO3:Ce3+ based on a combinatorial materials chip and high-throughput XRD. Issue 27 (23rd June 2021) - Liang, Shan-Shan; Huang, Meng; Wang, Yu; Li, Qian-Li; Yang, Xin-Xin; Zhao, Jing-Tai; Gao, Xing-Yu; Yin, Guang-Zhi; Liu, Qian; Zhang, Zhi-Jun
Abstract : The effect of Sc substitution on the crystal struture of LuBO3 :Ce 3+ based on high-effectively combinatorial materials method and high-throughput XRD. Abstract : A (Lu1− x Sc x )0.99 Ce0.01 BO3 (LSBO:Ce, x = 0–1) material library is successfully prepared via combinatorial materials technology, and the crystal structures are characterized via a high-throughput XRD platform at the Shanghai Synchrotron Radiation Facility (SSRF). The angular distortion increases upon the substitution of Lu 3+ with Sc 3+, as shown through crystal structure analysis of as-prepared LSBO:Ce, obtained via the Rietveld refinement method. LSBO:Ce shows obvious red shifts in its PLE and PL spectra with increasing Sc concentration because of an increased Stokes shift originating from an increased crystal field splitting effect and angular distortion. Owing to reduced symmetry, increased strain and the nephelauxetic effect will reduce energy transfer from charge carriers to Ce 3+ as luminescent centers. Due to greater loss during the energy conversion process, the PL intensity and decay time decrease with an increase in the Sc 3+ /Lu 3+ ratio. Based on high-throughput rapid and efficient screening, the optimized LSBO:Ce ( x = 0.2) material was selected to fabricate a scintillation screen with polymethyl methacrylate (PMMA) in order to study its scintillation properties. As the powder concentration increases from 0.5 to 10 wt%, the transmittance of the scintillation screen drops from 86 to 73.5%. It is of note that the integrated XEL intensity of the LSBO:Ce@PMMA scintillation screen is 1.36 times higher than that of a BGO single crystal. The spatial resolution of the scintillation screen can reach as high as 300 μm thanks to the intense XEL intensity and 80% transmittance in the visible light range. This study is of great significance for the potential application of LSBO:Ce in the fields of X-ray detection and imaging.